Macrophage Cell Activation with Acute Apical Abscess Contents Determined by Interleukin-1 Beta and Tumor Necrosis Factor Alpha Production - Sousa, Ezilmara L. R.; Martinho, Frederico C. [UNESP]; Leite, Fabio R. M.; Nascimento, Gustavo G.; Gomes, Brenda P. F. A. (Elsevier B.V., 2014)
Introduction: This clinical study has investigated the antigenic activity of bacterial contents from exudates of acute apical abscesses (AAAs) and their paired root canal contents regarding the stimulation capacity by levels of interleukin (IL)-1 beta and tumor necrosis factor alpha (TNF-alpha) throughout the root canal treatment against macrophage cells. Methods: Paired samples of infected root canals and exudates of AAAs were collected from 10 subjects. Endodontic contents were sampled before (root canal sample [RCS] 1) and after chemomechanical preparation (RCS2) and after 30 days of intracanal medication with calcium hydroxide + chlorhexidine gel (Ca[OH](2) + CHX gel) (RCS3). Polymerase chain reaction (16S rDNA) was used for detection of the target bacteria, whereas limulus amebocyte lysate was used to measure endotoxin levels. Raw 264.7 macrophages were stimulated with AAA exudates from endodontic contents sampled in different moments of root canal treatment. Enzyme-linked immunosorbent assays were used to measure the levels of TNF-alpha and 11-1 beta. Results: Parvimonas micra, Porphyromonas endodontalis, Dialister pneumosintes, and Prevotella nigrescens were the most frequently detected species. Higher levels of endotoxins were found in samples from periapical exudates at RCS1 (P < .005). In fact, samples collected from periapical exudates showed a higher stimulation capacity at RCS1 (P < .05). A positive correlation was found between endotoxins from exudates with IL-1 beta (r = 0.97) and TNF-alpha (r = 0.88) production (P < .01). The significant reduction of endotoxins and bacterial species achieved by chemomechanical procedures (RCS2) resulted in a lower capacity of root canal contents to stimulate the cells compared with that at RCS1 (P < .05). The use of Ca(OH)(2) + CHX gel as an intracanal medication (RCS3) improved the removal of endotoxins and bacteria from infected root canals (P < .05) whose contents induced a lower stimulation capacity against macrophages cells at RCS1, RCS2, and RCS3 (P < .05). Conclusions: AAA exudates showed higher levels of endotoxins and showed a greater capacity of macrophage stimulation than the paired root canal samples. Moreover, the use of intracanal medication improved the removal of bacteria and endotoxins from infected root canals, which may have resulted in the reduction of the inflammatory potential of the root canal content.
Keywords: Endodontics; endotoxins; instrumentation; root canal and abscess